Can “Nudge” Salvage Community Policing against Terrorism? - Li, Enshen (Terrorism and political violence, 2023)
Since the mid-2000s, the fear of “homegrown” terrorism in most developed democracies has prodded police to partner with local Muslim communities as a proactive and preventive approach to Islamic extremism. However, despite practical variations, this model of counterterrorism community policing (“CTCP”) has faced a comparable challenge—the lack of legal and moral legitimacy within counterterrorism law enforcement which erodes Muslim communities’ trust and confidence in policing. Drawing on common critiques of CTCP in the U.S., the U.K. and Australia, this article aims to proffer a behavioral-economics view to promote intended goals of CTCP. Borrowing the ideas of Nudge Theory, my discussion suggests that community engagement within CTCP could be stimulated more effectively through a subtle process of trust building whereby residents are coaxed toward cooperation through indirect encouragement, assistance and facilitation. Through a case study of CTCP in Muslim communities, it is argued that nudge entails the refrainment of the political and media narrative from conflating Islamist ideology with the prime source of domestic terrorist danger. At the grassroots level, the nudge-oriented CTCP is contingent upon community representatives taking on a more active and forefront role in CTCP with police reducing their visibility to only facilitate in the background.